Optimizing yield properties of bitter melon (Momordica charantia L.) plant by integrative application of poultry manure - Gulsum Yaldiz; Mahmut Camlica; Deniz Dasdemir (International Journal of Recycling of Organic Waste in Agriculture, 2025)
Purpose: Poultry manure has promising effects on bitter melon fruit yield and can be considered as a suitable substitute for chemical fertilizers. This study was conducted to determine the effect of chicken (CM) and turkey manure (TM) with a control on the bitter melon morphology and yield at the Agriculture Faculty research and application area of Bolu Abant İzzet Baysal University, Bolu, Türkiye in 2021 year.